Developing and Validating Contextual Learning Instructional Materials for Two-Variable Linear Equation Systems in Senior High School Mathematics - Maria Carmelita Tali Wangge (CV. SPDFHarmony, 2025)
Background: The quality of mathematics instruction is strongly influenced by the availability of well-designed instructional materials that actively engage students and connect abstract concepts to real-life contexts. In practice, mathematics learning at the secondary level often remains teacher-centered, limiting students’ opportunities to construct meaning independently. This condition is particularly evident in learning systems of linear equations in two variables, where procedural instruction dominates and contextual understanding is minimal. Therefore, developing instructional materials grounded in contextual learning principles is essential to improve instructional quality and learning effectiveness. Aims: This study aimed to develop and validate contextual learning-based instructional materials for the topic of two-variable linear equation systems at the senior high school level and to examine their effectiveness in supporting classroom learning. Methods: This research employed a development research design using a modified 4-D model, limited to the define, design, and develop stages. The instructional materials produced consisted of lesson plans, student worksheets, and achievement tests. Validation by subject-matter experts, classroom trials, and implementation phases were conducted to evaluate validity, practicality, and effectiveness. Data were collected through validation sheets, classroom observation instruments, student response questionnaires, and learning achievement tests. Results: The findings indicated that all instructional materials met the criteria of validity with expert evaluations categorized as good. Teachers’ instructional management was consistently rated effective, student learning activities aligned with planned instructional phases, and student responses toward the learning process were predominantly positive. Classical learning mastery was achieved, demonstrating the effectiveness of the developed materials. Conclusion: The study confirms that contextual learning-based instructional materials can significantly enhance the quality of mathematics instruction by fostering active student engagement, meaningful learning experiences, and improved learning outcomes. The integration of real-life contexts into mathematical instruction supports students’ conceptual understanding and problem-solving abilities. These findings contribute to instructional development research by providing empirically validated materials that align with contemporary pedagogical demands. The results also offer practical implications for mathematics educators seeking to implement contextual learning approaches and support curriculum innovation in secondary education settings.